2011
DOI: 10.1016/j.ajpath.2011.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Interactions of Epidermal Collagen XVII with the Extracellular Matrix

Abstract: The extracellular matrix (ECM) is not merely a supporting scaffold for tissue and organ architecture. The ECM can bind and release growth factors, which regulate many biologic processes and cell functions, including migration, differentiation, and proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
68
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 34 publications
3
68
0
1
Order By: Relevance
“…Consistent with this notion, we have shown that migrating keratinocytes constitutively shed and leave the collagenous ectodomain of collagen XVII in the extracellular matrix (22,23). However, the regulation mechanisms of collagen XVII ectodomain shedding are still unclear.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…Consistent with this notion, we have shown that migrating keratinocytes constitutively shed and leave the collagenous ectodomain of collagen XVII in the extracellular matrix (22,23). However, the regulation mechanisms of collagen XVII ectodomain shedding are still unclear.…”
supporting
confidence: 65%
“…For detection of the intracytoplasmic domain of collagen XVII, the polyclonal goat antibody N18 (Santa Cruz Biotechnology) was diluted 1:500. A new rabbit polyclonal antibody (Ab-SILP) was produced using the synthetic peptide NH 2 -SILPYGDS, as described previously (16,23). Purification of the Ab-SILP was performed using SulfoLink coupling resin (20404, Thermo Scientific) according to the manufacturer's instructions, and the final concentration of 1 g/ml of the antibody was used.…”
Section: In Silico Prediction and Targeting Potential Coiled Coils Onmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more detailed analysis is required to clarify the exact role of collagen XVII during glomerular development. At the dermal-epidermal junction, the main intracellular binding partners of collagen XVII are BP230, plectin and integrin β4 subunit, whereas the extracellular part of collagen XVII interacts with laminin-332 (α3β3γ2) and the integrin α6 subunit (Van den Bergh and Giudice 2003; Aumailley et al 2006;Mihai and Sitaru 2007;Nishie et al 2011). In mature kidney, the major integrin complex, α3β1, is located in the FPs of podocytes at the interface with GBM, Bowman's capsule, mesangial cells and the basal aspect of distal tubular cells (Adler 1992;Patrakka and Tryggvason 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Hemidesmosomes are multimolecular complexes that promote the stable adhesion of epithelial cells to the underlying extracellular matrix. COL17 is known to interact with BP230, plectin, a 6 b 4 integrin, laminin 332, and collagen IV (51)(52)(53). There is a possibility that COL17-humanized mice have less skin stability than do wild-type mice owing to the insufficient interaction between hCOL17 and other murine components, which may lead to skin fragility in COL17-humanized mice in a complement-independent manner, although we have shown that without the transfer of pathogenic Abs, neonatal COL17-humanized mice skin is intact (Tables I-IV).…”
Section: Discussionmentioning
confidence: 99%